Differences in the progression rate of SCTLD in Pseudodiploria strigosa are related to colony size and morphology - Camacho-Vite, Carolina; Estrada-Saldívar, Nuria; Pérez-Cervantes, Esmeralda; Alvarez-Filip, Lorenzo (Frontiers in Marine Science, 2022)
Stony Coral Tissue Loss Disease (SCTLD) impacts are unprecedented concerning the level of devastation they have imposed on Caribbean coral assemblages. Although SCTLD affects nearly 30 different coral species, it has been particularly lethal for Pseudodiploria strigosa. Mortality rates for this species are estimated to be between 60 and 100% in the Caribbean; however, tissue-loss rates have been shown to differ among colonies, which suggests that colony health, environmental conditions, and concurrent transmission events are crucial to the development of the disease at reef scale. To gain insight into the colony-level dynamics of SCTLD, we used a simplified photogrammetry and 3D modeling approach to quantify and compare SCTLD-related tissue-loss rates among 20 colonies of P. strigosa on a shallow back-reef in the Mexican Caribbean. Over a six-month period, SCTLD resulted in the full mortality of 70% of the colonies that were tagged shortly after infection. Although disease progression followed a multifocal-type infection in most cases, tissue-loss rates significantly differed among colonies. Some colonies died within the first 20 days of observation, while others died towards the end of the study period. We found a significant positive effect of colony size on rates of tissue loss disease, as well as evidence suggesting that elongated and vertically compressed colonies have a greater probability of experiencing higher tissue-loss rates than colonies with more spherical shapes. The observed relationship between colony morphology and tissue-loss rates is likely a result of elongated colonies having more flat surface area at the top of the colonies which facilitates accumulation of sediments, which have been shown to be a source of SCTLD transmission.